PENGARUH VARIASI DEBIT ALIRAN TERHADAP GERUSAN MAKSIMAL DI BANGUNAN JEMBATAN DENGAN MENGGUNAKAN PROGRAM HEC-RAS - Ichsanul Barokah, Didik Purwantoro (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2014)
This research aims to find The maximum scour depth occurred in building bridges using HEC -RAS software . Maximum scour modeling results can be used to identify and estimate thestability of the structure of the bridge. This research using software HEC-RAS v. 4.1.0. Stagesof modeling programming includes several data input process, that is: the geometry data inputstream, bridge geometry data input, input the data flow, data input on bridge scour. Modeling isdone with the flow rate changes on any one process is running. Modelling maximum scour whoreviewed that is on the pillars of the bridge. This research result of this modeling with the flowrate variation, it can be seen that the discharge 5.87 m³ / s to 905.23 m³ / s began to increasethe depth of scour at the pillars. Then on debit 905.23 m³ / s to 1080.15 m³ / s scour depthexperience stability pillar, at a depth of 1.76 m..Keyword: HEC-RAS, Scour, The flow rate